PENGARUH TEKNOLOGI INFORMASI DAN KOMPETENSI APARATUR PENGELOLA KEUANGAN TERHADAP KUALITAS INFORMASI AKUNTANSI PADA SKPD DI KOTA MANADO - Nantingkaseh, Ribka L.V; Ilat, Ventje; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Quality of accounting information is a normative prerequisite that must be met in the preparation of financial statements so that accounting information generated can be useful for users of financial statement. This study aims to determine the effect of information technology and the competence of the financial management apparatus on the quality of accounting information on SPKD in Manado City. The data collected by through the spreading of questionnaires to 50 respondents which is the apparatus of financial management at SKPD in Manado City. The data were analyzed by using multiple linear regression analysis method with the help of SPSS 23 program. The result of this research indicates that information technology and competence of financial management apparatus have a positive and significant influence on the the quality of accounting information at SKPD in Manado City.Keywords : Information technology, Competence of financial management apparatus, Qualityof accounting information